Intestinal alkaline phosphatase (IAP, IAP Enhancer) attenuates intestinal inflammation and alleviates insulin resistance - Gao, Chenzhe; Koko, Marwa Yagoub Farag; Ding, Mingxing; Hong, Weichen; Li, Jianping; Dong, Na; Hui, Mizhou (Frontiers in Immunology, 2022)
In this study, we investigated the effects of intestinal alkaline phosphatase (IAP) in controlled intestinal inflammation and alleviated associated insulin resistance (IR). We also explored the possible underlying molecular mechanisms, showed the preventive effect of IAP on IR in vivo, and verified that the dephosphorylation of IAP for the inhibition of intestinal inflammation in vitro. Furthermore, we examined the preventive role of IAP in IR induced by a high-fat diet in mice. We found that an IAP + IAP enhancer significantly ameliorated blood glucose, insulin, low density lipoprotein, gut barrier function, inflammatory markers, and lipopolysaccharide (LPS) in serum. IAP could dephosphorylate LPS and nucleoside triphosphate in a pH-dependent manner in vitro. Firstly, LPS is inactivated by IAP and IAP reduce LPS-induced inflammation. Secondly, adenosine, a dephosphorylated product of adenosine triphosphate, elicited anti-inflammatory effects by binding to the A2A receptor, which inhibits NF-κB, TNF, and PI3K-Akt signalling pathways. Hence, IAP can be used as a natural anti-inflammatory agent to reduce intestinal inflammation-induced IR.